The Impact of Surface Conditions on Natural Gas Filtration Process under Reservoir Conditions - Mirza A. Dadash-Zade; Cao, Ru (International Journal of Electric Power and Energy Studies, 2024)
The analysis indicates that by this time, the term "model" has already been widely disseminated. Using such models, different process details can be defined to obtain necessary parameters or verify proposed assumptions. It is important to note that modeling does not replace the study of the object; rather, it serves as a supplementary source of information about the reservoir or well, and it is also used in modeling.